Functional analysis of germline ETV6 W380R mutation causing inherited thrombocytopenia and secondary acute lymphoblastic leukemia or essential thrombocythemia. (18th August 2021) - Kozubik, Katerina Stano; Radova, Lenka; Reblova, Kamila; Smida, Michal; Zaliova Kubricanova, Marketa; Baloun, Jiri; Pesova, Michaela; Vrzalova, Zuzana; Folber, Frantisek; Mejstrikova, Sona; Pospisilova, Sarka; Doubek, Michael
Abstract: Germline mutations in ETV6 gene cause inherited thrombocytopenia with leukemia predisposition. Here, we report on functional validation of ETV6 W380R mutation segregating with thrombocytopenia in a family where two family members also suffered from acute lymphoblastic leukemia (ALL) or essential thrombocythemia (ET). In-silico analysis predicted impaired DNA binding due to W380R mutation. Functional analysis showed that this mutation prevents the ETV6 protein from localizing into the cell nucleus and impairs the transcriptional repression activity of ETV6. Based on the germline ETV6 mutation, ET probably started with somatic JAK2 V617F mutation, whereas ALL could be caused by diverse mechanisms: high-hyperdiploidity; somatic deletion of exon 1 IKZF1 gene; or somatic mutations of other genes found by exome sequencing of the ALL sample taken at the diagnosis.